Low doses of multi-walled carbon nanotubes elicit hepatotoxicity in rats with markers of oxidative stress and induction of proinflammatory cytokines (2018)
The investigation into the potential health risks associated with the use of engineered nanoparticles is a major scientific interest in recent years. The present study elucidated the involvement of proinflammatory cytokines, cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) in carboxylated multi-walled carbon nanotubes (MWCNTs)-induced hepatotoxicity. Pubertal rats were exposed to purified MWCNTs at 0, 0.25, 0.50, 0.75 and 1.0 mg/kg for 5 consecutive days. Results indicated that exposure to MWCNTs caused liver damage evidenced by significant elevation in serum activities of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP) and gamma glutamyl transferase (GGT) when compared with control. Moreover, MWCNTs significantly decreased superoxide dismutase (SOD) and glutathione S-transferase (GST) activities as well as glutathione level whereas it significantly increased catalase (CAT) and glutathione peroxidase (GPx) activities in liver of the treated rats. Moreover, the dose-dependent increase in hepatic hydrogen peroxide (H2O2) and lipid peroxidation levels were accompanied by marked increase in micronucleated polychromatic erythrocytes (MNPCE) in the MWCNTs-treated rats. Administration of MWCNTs significantly increased serum concentrations of pro-inflammatory cytokines namely interleukin-1b (IL-1b), interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-a) in the treated rats. Immunohistochemical analysis showed significantly increased COX-2 and iNOS protein expressions in the liver of MWCNTs-treated rats. In conclusion, carboxylated MWCNTs induces hepatic damage via disruption of antioxidant defense systems, promotion of pro-inflammatory cytokines generation and expression of COX-2 and i-NOS in rats.